2008
DOI: 10.1002/elps.200800086
|View full text |Cite
|
Sign up to set email alerts
|

Epstein–Barr virus upregulates phosphorylated heat shock protein 27 kDa in carcinoma cells using the phosphoinositide 3‐kinase/Akt pathway

Abstract: Gastric cancer is the most common cancer in Japan and infection with Epstein-Barr virus (EBV) is responsible for about 10% of gastric cancers worldwide. Although EBV infection may be involved at an early stage of gastric carcinogenesis, the mechanisms underlying its involvement remain unknown. To investigate the role of EBV in gastric carcinogenesis, we performed proteomic analyses of an EBV-infected gastric carcinoma cell line NU-GC-3 (EBV(+)) and its uninfected control (EBV(-)). 2-DE was combined with MS to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 52 publications
0
23
0
Order By: Relevance
“…Several observations point to a role for Akt as Hsp25/27 kinase [94,[98][99][100][101][102]. First, the Akt1, Akt2, and Akt3 isoforms can bind directly to Hsp27 and can be found in a complex with p38 MAPK, MK2, and Hsp27 [98][99][100].…”
Section: Akt/protein Kinase B (Pkb)mentioning
confidence: 99%
See 1 more Smart Citation
“…Several observations point to a role for Akt as Hsp25/27 kinase [94,[98][99][100][101][102]. First, the Akt1, Akt2, and Akt3 isoforms can bind directly to Hsp27 and can be found in a complex with p38 MAPK, MK2, and Hsp27 [98][99][100].…”
Section: Akt/protein Kinase B (Pkb)mentioning
confidence: 99%
“…Second, Rane and colleagues showed that Akt could phosphorylate Hsp27 at Ser-82, but not Ser-15 or Ser-78, in vitro, while co-expression of an active Akt mutant and Hsp27 in HEK cells resulted in Hsp27 phosphorylation at the same residue [100]. Third, comparative proteomic analysis of the gastric carcinoma cell line NU-GC-3 with Epstein-Barr virus (EBV)-infected cells revealed increased phosphorylation of Hsp27 at Ser-82 in an Akt-dependent, but MEK/ERK-and p38 MAPK-independent, manner [101]. Total protein levels of phosphoAkt, but not Akt, MK2 or phosphoMK2, were increased, suggesting that phosphorylated (activated) Akt controls EBV-induced Hsp27 phosphorylation.…”
Section: Akt/protein Kinase B (Pkb)mentioning
confidence: 99%
“…To examine the possible involvement of the PI3-K/Akt pathway in TGF-␤1-induced EBV reactivation, the expression of EBV lytic proteins was analyzed in TGF-␤1-stimulated Mutu-I, Kem-I, and Sav-I cells, pretreated with increasing concentrations of wortmannin, a selective inhibitor of PI3-K activity (30,31), or Akt inhibitor X, a specific pharmacological inhibitor of Akt (32). As illustrated by Fig.…”
Section: Tgf-␤1-activated Pi3-k/akt Signaling Pathway Is Required Formentioning
confidence: 99%
“…Of the kinases shown to catalyze the phosphorylation of hsp27, PKC is lipid-dependent and the experiments conducted herein were performed without lipid and in the presence of EGTA plus a peptide inhibitor of PKA (PKI, 1 μM); hence, these kinases would not be active. PKB forms a complex with [50] and phosphorylates hsp27 [41,42]. However, activated PKB requires higher [NaCl] to elute from Mono Q than observed for the hsp27 kinase activities reported herein.…”
Section: Discussionmentioning
confidence: 64%
“…Hsp27 is phosphorylated by several protein kinases, including PKA [40], PKB [41,42], PKC [40,43], PKD [44], PKG [45], MK2 [46], MK3 [47], and MK5/PRAK [48,49] in vitro ( Fig. 1, reviewed in [8]).…”
Section: Discussionmentioning
confidence: 99%